Vozes silenciadas: o imaginário e a tragédia anunciada na ópera dos mortos, de Autran Dourado - Torinho, Maria Esther (2017)
Taking into account the thought-provoking title of the literary work – Opera of the dead, along with the ambiguity which is part of the mansion, stage of the narrative, which reflects on the main character’s behavior and transforms her in a conflictive subjectivity, and at the same time announces a tragedy which at the end turns out to be real, and the presence of highly meaningful images, which contribute for a permanent tension in the literary work, we intend to investigate how the main character contributes for the accomplishment of the tragedy. In order to achieve this purpose, we analyse the role of those images, taking as a theorical support Gaston Bachelard’s theory about the four elements – water, air, fire and earth, and, specially, Gilbert Durand’s theory about the imagen regimes. In what concerns to tragedy, we analyse the main character’s attitude according to the concepts of the classical tragedy commented by Aristotle in his Poetical Art, some of them updated. Thus, we notice that in this conflict between Eros and Thanatos, the images act differently: while some of them are symbols of death, some others act as a way of struggling against death entailed by time and the main character contributes, with her excess, to death to defeat life, leading to the consummation of the tragedy and causing the narrative voices to be mute.